Traveling wave solutions and conservation laws of some fifth-order nonlinear equations - İnç, Mustafa; Aliyu, Aliyu Isa; Yusuf, Abdullahi (Springer Heidelberg, 2017)
In this paper, the Riccati-Bernoulli sub-ODE method is used to find the soliton solutions of two different fifth-order nonlinear partial differential equations (NPDEs). The efficiency of this method for finding exact and traveling wave solutions has been demonstrated. The solitons appear with all necessary constraint conditions which guarantee their existence. The conservation laws (Cls) for the underlying equations are constructed using the Ibragimov's Cls theorem. The obtained solutions have been demonstrated by some figures.
Keywords: Optical Solitons; Dispersion; Explicit; Power; Kerr